2020
DOI: 10.28945/4518
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis to Understand the Online Learners’ Success in Public Higher Education in Morocco

Abstract: Aim/Purpose: This study focuses on the learners’ success toward learning management systems in higher education in Morocco and also proposes a theoretical model to better understand the determinants of learners’ satisfaction, self-regulation and continuance intention to use these systems. For this purpose, variables which may have a positive or negative influence in our model are examined. Background: The latest version of the technology acceptance model, expectation–confirmation model, DeLone and McLean Info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
50
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 54 publications
(142 reference statements)
6
50
0
2
Order By: Relevance
“…This, in turn, reflected on the acquisition and development of students' instructional software design skills. This result is consistent with studies of Wei et al [45]; Hughes et al [25]; and Patrick and Powell [37] that have demonstrated the effectiveness of AR on the acquisition and development of skills. On the other hand, we find the control group, which was studied according to the virtual classrooms without using AR, and whose students were allowed to view the recorded lectures an unlimited number of times, did not excel as did the experimental group in the acquisition and development of instructional software design skills, which may be due to two factors.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This, in turn, reflected on the acquisition and development of students' instructional software design skills. This result is consistent with studies of Wei et al [45]; Hughes et al [25]; and Patrick and Powell [37] that have demonstrated the effectiveness of AR on the acquisition and development of skills. On the other hand, we find the control group, which was studied according to the virtual classrooms without using AR, and whose students were allowed to view the recorded lectures an unlimited number of times, did not excel as did the experimental group in the acquisition and development of instructional software design skills, which may be due to two factors.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, the nature of the content and the appropriateness of its procedures for learning through ODL is also important. In this regard, studies of Hughes et al [25]; Patrick and Powell [37] have shown that the effectiveness of both virtual classrooms and virtual schools through e-learning in general increased student academic achievement and skills. This is consistent with a study by Barbour and Mulcahy [7], who investigated the role of virtual classrooms in ODL in increasing the academic achievement and skills of high school students who live in remote places compared to their colleagues who study in traditional classrooms.…”
Section: Online Distance Learningmentioning
confidence: 99%
“…The fields mentioned above have been shaped by the intersection of ICTs, teaching, and learning. At service and technology levels, such interest has increased the utilization of a variety of platforms that provide online courses, administer elearning activities, report learners' and lecturers' learning and teaching performances, and inform education-related decisions [15][16][17]. According to the latest reports, the majority of industries (up to 98%) around the world will implement e-learning with the purpose of having a digital learning strategy by the end of 2020 [18][19].…”
Section: Related Workmentioning
confidence: 99%
“…In our previous research (Safsouf, Mansouri and Poirier, 2018, 2019, 2020, we identified and classified several factors, which allowed us to explain satisfaction, self-regulation, intention to continue using and success in an LMS. These factors were derived from several models: the TAM3 model (Venkatesh and Bala, 2008), the Expectation Confirmation Model (ECM) (Bhattacherjee, 2001), the DeLone and McLean Information Success Systems Model (D&M ISS) (Delone and Mclean, 2003) and the Self-Regulated Learning Theory (SRL) (Zimmerman, 2013), (Panadero, 2017).…”
Section: Ux Measurement Factorsmentioning
confidence: 99%